2022
DOI: 10.3389/fnins.2022.889689
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression and Correlation Analysis of Global Transcriptome for Hemorrhagic Transformation After Acute Ischemic Stroke

Abstract: In order to explore the epigenetic characteristics of hemorrhagic transformation (HT) after acute ischemic stroke, we used transcriptome sequencing technology to analyze the global transcriptome expression profile of patients with and without HT after acute ischemic stroke and to study the differential expression of messenger RNA (mRNA), long noncoding RNA (lncRNA), circular RNA (circRNA) and mircoRNA (miRNA) between the two groups. To further explore the role of differentially expressed genes in HT, we annota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…There were 47 significantly differentially expressed microRNAs from peripheral blood in patients with HT compared with those without HT. MiRNA-383-5p was one of the top ten down-regulated microRNAs related to HT, similar to our study [21]. In the transient MCAO model of wild-type mice, miRNA-155 increased in the peri-infarct regions, which regulated BBB permeability via direct interactions with several mRNAs.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…There were 47 significantly differentially expressed microRNAs from peripheral blood in patients with HT compared with those without HT. MiRNA-383-5p was one of the top ten down-regulated microRNAs related to HT, similar to our study [21]. In the transient MCAO model of wild-type mice, miRNA-155 increased in the peri-infarct regions, which regulated BBB permeability via direct interactions with several mRNAs.…”
Section: Discussionsupporting
confidence: 87%
“…Our study provides new evidence for the association of microRNAs with PH in AIS after mechanical reperfusion therapy. Most differentially expressed microRNAs were not reported to be involved in PH after reperfusion [20,21,[36][37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regulating microRNAs in the BBB may alleviate CIRI in animal and in vitro models with OGD/R. [8][9][10][11][12][13][14][15][16][17][18] In this study, we found microRNA-29a-5p decreased in astrocytes after OGD/R. Increased microRNA-29a-5p alleviated astrocyte injury and induced phenotype shifting of astrocytes.…”
Section: Discussionmentioning
confidence: 48%
“…PTH1R may also be associated with the risk of autism spectrum disorder . In addition, although a potential association between PTH1R or PTH1R and IS has not been investigated, the calcium-ion signaling pathway and neuroactive ligand–receptor interaction pathways have been established as key pathways in IS and post-IS hemorrhagic transformation. Furthermore, regulating the neuroactive ligand–receptor interaction pathway also regulates ferroptosis in vascular neuronal cells, thereby affecting the occurrence and development of hypertension and IS …”
Section: Discussionmentioning
confidence: 99%